Problem Based Learning (PBL) Learning Model in Indonesian Language Lessons to Improve Writing Skills Argumentation Paragraph for Class VIII MTS YAPPAM Martebing Students - Manurung, Rusda (Universitas Negeri Padang, 2024)
This research aims to produce a Problem Based Learning(PBL) learning model to improve the ability to write practical and effective argumentative paragraphs. An argumentative paragraph is a paragraph that expresses an opinion accompanied by accurate evidence and facts to convince the reader. Therefore, to train students' skills in writing argumentative paragraphs, students must be trained optimally and given maximum understanding to improve their understanding in writing argumentative paragraphs. This type of research is development research ( Research and Development ) using the Borg & Gall development model. The subjects of this research were 30 students of class VIII MTS YAPPAM. Data analysis was carried out by converting the total actual scores obtained into five-scale qualitative data. The products developed are PBL learning model books, lesson plans, worksheets (LK) and learning achievement tests (TPB). The results of expert validation, teacher assessment scores, student responses, learning observations, learning achievement tests, and investigative ability tests show that PBL learning model books, lesson plans, worksheets (LK), learning achievement tests (TPB), and argumentative paragraph writing ability tests (TKMPA) is valid, practical and effective. Thus, overall the research conducted shows that the product developed is suitable for use in terms of validity, practicality and effectiveness. Keywords: development of learning models, problem based learning , argumentative paragraph.